Metode Mengurangi Kecanduan Gadjet dan Meningkatkan Prestasi Dengan Mengenal Gaya Belajar Anak - Muhammad Zainal Roisul Amin; Adi Mulyadi; Lestyo Wulandari; Bambang Sri Kaloko (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Addiction to gadgets or devices can occur in children or adults. Addiction can happen to anyone, whether they are children or adults. So, if someone becomes addicted to gadgets. The cause of gadget addiction is the habit of interacting without rules, leading people to increasingly feel the pleasure and addiction of interacting in the virtual world. Gadget addiction is very dangerous when experienced by children because it poses problems for them including a lack of socialisation with friends as they already have virtual friends, not communicating with those around them, and health issues such as eyesight problems that can affect a child's emotional stability. From these issues, it is necessary to educate parents to always accompany and limit their children while playing with gadgets. Many parents do not understand how to support their children while playing with gadgets, which is one of the challenges faced by parents at Khodijah 112 Dadapan Kindergarten. Therefore, it is important to raise awareness among parents about how to support their children so that they do not become addicted to gadgets and how parents can understand their children's learning methods to improve their academic performance.